Electrokinetic properties of PMAA functionalized NiFe2O4 nanoparticles synthesized by thermal plasma route - Bhosale, Shivaji V.; Mhaske, Pravin; Kanhe, N.; Navale, A. B.; Bhoraskar, S. V.; Mathe, V. L.; Bhatt, S. K. (Solid State Physics: Proceedings of the 58th Dae Solid State Physics Symposium 2013, PTS A & B, 2014)
The magnetic nickel ferrite (NiFe2O4) nanoparticles with an average size of 30nm were synthesised by Transferred arc DC Thermal Plasma route. The synthesized nickel ferrite nanoparticles were characterized by TEM and FTIR techniques. The synthesized nickel ferrite nanoparticles were further functionalized with PMAA (polymethacrylic acid) by self emulsion polymerization method and subsequently were characterized by FTIR and Zeta Analyzer. The variation of zeta potential with pH was systematically studied for both PMAA functionalized (PNFO) and uncoated nickel ferrite nanoparticles (NFO). The IEP (isoelectric points) for PNFO and NFO was determined from the graph of zeta potential vs pH. It was observed that the IEP for NFO was at 7.20 and for PNFO it was 2.52. The decrease in IEP of PNFO was attributed to the COOH functional group of PMAA.
Keywords: IEP; NiFe2O4; PMAA; Thermal plasma; Zeta potential